2018
DOI: 10.1136/bmjopen-2017-021175
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and complications of lower limb cellulitis in Africa: a systematic review

Abstract: ObjectiveTo summarise available data on the risk factors, complications and the factors associated with complications of lower limb cellulitis in Africa.MethodsWe did electronic searches on PubMed, EMBASE, Scopus and African Journals Online from 1 January 1986 to 30 October 2017, extracted and summarised data on the risk factors, complications and the factors associated with the complications of lower limb cellulitis from eligible literature.ResultsA total of seven studies were retained for final review after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
3
19
1
1
Order By: Relevance
“…Moreover, in 2015, cellulitis accounted for 1447 disability adjusted life years (DALYs) in Cameroon and affected mostly men and members in the lower class of society [9, 10]. It is also associated with a prolonged hospital stay, with resultant reduction in income and economic productivity, and consequent worsening of the vicious cycle of poverty [911]. The burden of cellulitis has been envisaged to increase in subsequent years in Africa due to the presence of factors such as increasing prevalence of obesity and voluntary depigmentation of the skin [11].…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, in 2015, cellulitis accounted for 1447 disability adjusted life years (DALYs) in Cameroon and affected mostly men and members in the lower class of society [9, 10]. It is also associated with a prolonged hospital stay, with resultant reduction in income and economic productivity, and consequent worsening of the vicious cycle of poverty [911]. The burden of cellulitis has been envisaged to increase in subsequent years in Africa due to the presence of factors such as increasing prevalence of obesity and voluntary depigmentation of the skin [11].…”
Section: Main Textmentioning
confidence: 99%
“…This difference is probably because the obesity index of the population we serve is 9% [ 15 , 16 ], which differs from the 40% and 29% reported for the US [ 17 ] and England [ 18 ], which are developed countries. In contrast, Tianyi et al published a review of SSTIs in Africa and showed that the major risk factor for complicated SSTIs was obesity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Cellulitis, which is often caused by gram positive bacteria, results in prolonged hospital stay and can have considerable morbidity and mortality if complications ensues. 27 The local complications are abscess and necrotizing fasciitis whereas the systemic complication is septic shock. 20,27 Often, primary cellulitis can result from trauma which could be recognizable or unrecognizable.…”
Section: Discussionmentioning
confidence: 99%
“…27 The local complications are abscess and necrotizing fasciitis whereas the systemic complication is septic shock. 20,27 Often, primary cellulitis can result from trauma which could be recognizable or unrecognizable. In Nassaji et al series, 38.2% of patients had history of trauma.…”
Section: Discussionmentioning
confidence: 99%